The lack of evidence for an association between cancer biomarker conversion patterns and CTC-Status in patients with metastatic breast cancer - Stefanovic, Stefan; Deutsch, Thomas M.; Riethdorf, Sabine; Fischer, Chiara; Hartkopf, Andreas; Sinn, Peter; Feißt, Manuel; Pantel, Klaus; Golatta, Michael; Brucker, Sara; Sütterlin, Marc; Schneeweiss, Andreas; et al. (International journal of molecular sciences, 2020)
Circulating tumor cell (CTC) detection is a prognostic factor in the metastatic breast cancer (MBC) setting. Discrepancies in primary (PT) and metastatic tumor (MT) genetic profiles are also of prognostic importance. Our study aimed to compare the CTC statuses and prognoses between those with subtype stable MBCs and MBCs with specific biomarker conversions. The study enrolled 261 MBC patients, treated at the National Center for Tumor Diseases, Heidelberg, Germany in a five-year period. All underwent PT and MT biopsies and subsequent CTC enumeration before the initiation of systemic therapy. ER and HER2 statuses of the PTs and MTs were determined and progression free survivals (PFSs) and overall survivals (OSs) were recorded. We compared CTC statuses, CTC counts, PFSs and OSs between subgroups of patients with different receptor change patterns. Patients who had tumors that converted to triple negative MTs had the shortest median OSs, while HER2 expression was not associated with a shorter median OS. No significant differences in PFSs and OSs have been demonstrated by Kaplan-Meier curve comparisons in any of the subgroup analyses. CTC counts were similar in all subgroups. CTCs were comparably less frequently detected in patients with a stable HER2 expression. Similar proportions of CTC positives were observed in all other subtype change pattern subgroups, barring the aforementioned HER2 stable subgroup. The detection of CTCs was of no appreciable prognostic value in different receptor change pattern subgroups in our cohort.
Gesehen am 16.06.2020